Controlled Multichannel Surface Plasmon Polaritons Transmission on Atomic Smooth Silver Triangular Waveguide. Issue 21 (20th August 2019) - Zhang, Tingting; Wang, Chi; Chen, Huan; Zhang, Chengyun; Zhang, Zhenglong; Fang, Yurui; Zheng, Hairong
Abstract: The application of plasmonic devices is considered as one promising solution for overcoming the limitation of traditional electronic devices. The critical challenges of plasmonic transmission devices include the control accuracy of large‐scale signal transmission and energy loss reduction. The 2D plasmonic waveguide provides a good platform on surface plasmon polaritons (SPPs) multimode excitation and emission manipulation. Here, an atomic smooth triangular waveguide with controllable multichannel transmission and relative long 1/e decay length is demonstrated. Corresponding SPPs excitation and propagation process are investigated through far‐field and near‐field distributions both experimentally and numerically. It is found that two different SPPs propagation modes can be selectively excited and supported on the surface of the 2D waveguide, and the propagation path can be controlled by the interference of the SPPs modes. The collimated beams with tunable period are also achieved on this waveguide via utilizing the interference between the reflected SPPs and the SPPs propagating from the other side of the plate through the edge. This work provides high‐performance 2D plasmonic waveguides with a comprehensive analysis of surface plasmon, which may have potential applications in 2D microplate‐based integrated photonic devices. Abstract : Atomic smooth triangular waveguides with controllable multichannel transmission and long decay length are demonstrated. Two SPPs modes can be selectively excited on the waveguide. The propagation paths can be controlled by the interference of the SPPs modes. This work provides high‐performance 2D plasmonic waveguides with comprehensive analysis of surface plasmon, which may have potential applications in microplate‐based integrated photonic devices.